Application of cognitive screening guidelines by health care providers in diabetes care: A cross‐sectional descriptive study. Issue 5 (29th November 2018) - Cuevas, Heather; Ward, Catherine
Abstract: Rationale, aims, and objectives: The risk of cognitive dysfunction is higher in people with diabetes than in the general population, and approximately 50% of those with diabetes will develop cognitive impairments as they age. Screening for cognitive dysfunction in people with diabetes can help identify both pathology and those who are at risk for higher health care utilization, but we do not know how health care providers implement cognitive screening recommendations in this population. In this study, we examined health care providers' knowledge of those recommendations and their application of them, as well as factors associated with guideline use. Methods: This study used a cross‐sectional, descriptive correlational design with a convenience sample. All data were collected with a 20‐question online survey sent to advanced practice nurses (APNs), medical doctors/doctor of osteopathic medicines (MDs/DOs), and physician assistants (PAs) in Central Texas. Results: One‐hundred eighty‐one health care providers responded. Participants most frequently said they were "moderately familiar" with guidelines for cognitive impairment screening (60.9%). Twenty‐three per cent of physicians, 37.4% of APNs, and 8.3% of PAs indicated that they incorporated routine screening into daily practice. However, 64% did not use standardized tools to assess cognitive function. The most common clinical tasks related to cognitive screening were referral for more in‐depth cognitive screening (44%) and education of families regarding cognitive problems (29%). Lack of time was the most common barrier to screening (57.7%). Conclusions: Most respondents believed that there was a good rationale for assessing cognitive function in people with diabetes. However, despite some familiarity with guidelines for cognitive function screening, most respondents did not use standardized assessment tools. The results indicate variability in clinical practice regarding assessment and practices, such that there may be some variability in outcomes for patients.